MASSER AF GRUNDE TIL USIKKER SEX: En undersøgelse af gode forklaringer - Dahl, Anders (Tidsskriftet Antropologi, 1996)
Anders Dahl: Plenty of Reasons for Unsafe Sex. An Investigation of Good Explanations Information campaigns on HIV/AIDS have been running for more than ten years, but still it is difficult to demonstrate any changes in the sexual behaviour of the Danish population, except in regard of men who have sex with men. Analyses of dialogues of telephone counselling at the AIDS Hotline in Copenhagen give insights into the explanations that counselling-seeking persons themselves give conceming their unsafe sexual behaviour. It appears that safe sex is generally considered easy and simple, and therefore instances of unsafe sexual behaviour come to be regarded as “slips” and not as a pattem of behaviour. Choices of sexual behaviour are not determined by knowledge alone, but also by culturally informed personal experience and the context of the sexual act. The article points towards a new strategy in future HIV/AIDS-related work, putting greater emphasis on dialogue with people with risk behaviour, e.g. in connection with HIV-testing. The use of the data collected at the hotline demonstrates new paths in the difficult field of sex research. Also, it appears from the data that the study of the so-called risk groups for HIV is probably not the most useful way to reach an understanding of sexual risk taking, as reasons for unsafe sex transcend such groups.